Forests, law and customary rights in Indonesia: Implications of a decision of the Indonesian Constitutional Court in 2012. (12th November 2018) - Hidayat, Herman; Yogaswara, Herry; Herawati, Tuti; Blazey, Patricia; Wyatt, Stephen; Howitt, Richard
Abstract : This paper reviews the emerging effects of the 2012 decision of the Constitutional Court of Indonesia relating to the customary management of Indonesia's traditional forests. It focuses on the challenge of moving from legal to political and societal recognition of Indigenous peoples' rights. In its advocacy of customary land rights, Aliansi Masyarakat Adat Nusantara (AMAN) successfully applied to the Constitutional Court for judicial review of the Forest Law 41 1999. It argued the law breached the constitutional rights of its members in permitting the state to permit exploitation and development rights over traditional forest without their consent. The flow‐on effect of allocating such rights included widespread deforestation and land use change without agreement from customary communities that have used and occupied these forests for centuries, thus ignoring traditional customary law that regards these forests as the property of such communities. The paper reflects critically on international experience in the interface between legal recognition of Indigenous peoples' rights, and their translation into sustainable and meaningful societal transformation.